Fostering academic excellence - McLeod, John, 1925- (Pergamon Press, 1989)
This book contains a general introduction to the education of academically able students. It provides a solid background of basic knowledge and a survey of research and theory for educational theorists, student teachers, practising teachers, administrators and planners. It offers insights into relevant practical problems as well as guidelines for classroom practice. The significance of this material is outlined for the various levels of the educational system from the individual classroom to the regional planning level. The book is not, however, designed to offer set answers and pat solutions, but to provide rationale for the creative work of teachers and administrators.